2020
DOI: 10.14341/dm10202
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia and the risk of cognitive impairment and dementia in elderly and senile patients with type 2 diabetes

Abstract: Research results show that poor glycemic control and recurrent episodes of severe hypoglycaemia are associated with a decrease in cognitive function in elderly people with type 2 diabetes mellitus (T2DM). On the other hand, patients with diabetes mellitus associated with cognitive impairment/dementia are most at risk of developing hypoglycaemic conditions. It is obvious that the relationship between hypoglycaemia and dementia is very complex and has a mutually aggravating nature. Studies also show that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…Cognitive disorders develop in over 50% DM2 patients and directly affect the quality of life, labour and social adaptation of these patients [8][9][10][11][12]. Assessment of cognitive disorders using MoCA has shown that the median score in the DM2 patients is reliably lower than that of the healthy volunteers in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive disorders develop in over 50% DM2 patients and directly affect the quality of life, labour and social adaptation of these patients [8][9][10][11][12]. Assessment of cognitive disorders using MoCA has shown that the median score in the DM2 patients is reliably lower than that of the healthy volunteers in the control group.…”
Section: Discussionmentioning
confidence: 99%